"The beguiled" de Sofia Coppola: o feminino na tela - Mussareli, Júlia Machado (2018)
This dissertation aims to problematize, under the category of gender analysis, Cultural History and Semiotics, the feature film "The Beguiled" through the eyes of director Sofia Coppola. The research goes through the theories of the History of Culture and Arts making it possible to identify and question the continuities and ruptures of the feminine local / universal / global North American in contemporary times considering the cinema as historical document. The analysis methodology interweaves the history of the present (director's perspective) with the history of the past (space and time of the plot). It identifies the permanences and transformations of the historical, social and cultural construction of the feminine in the female characters, as well as the generational relations, the representations of the past / present and the social imaginaries in the plot, without losing sight of the real / a woman filmmaker. The research also traces the trajectory of personal and professional life of the filmmaker to understand her reading on literary and cinematographic narratives; similarly wanders over the book "A Painted Devil" written by Thomas Cullinan that served as inspiration for Coppola and Siegel to produce the film; likewise runs through the first version of the film, produced by Don Siegel in the 70's and the male figure. Without the pretension of analyzing them, the book and the first version of the film contribute to the perception of the transposition to the remake of Coppola, supports the proposed verification and provides the theoretical-methodological basis of the central problematic. Finally, he enters the field of Gesltat for a more complete analysis of the film from the feminine look of Coppola.